Morphological Characteristics of Local Varieties of Tobacco Applied with Biochar-Based Slowrelease Fertilizer on Clay Textured Soils . - Sukardi, Sukardi; Zamzam, Syamsiar; Sukmawati, Sukmawati; Qadri, Sri Nur; Rahim, Iradhatullah (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
Local tobacco has an important role in the kretek cigarette industry in Indonesia, because 80% of kretek cigarettes are made using local tobacco. However, in some areas, the quality of local tobacco remains low due to inefficient fertilisation. Using slow-release fertiliser can increase the efficiency of nutrient uptake by plants. This Research aims to examine the use of biochar-based slow-release fertiliser on the morphological characteristics of tobacco plants. The Research method was a field experiment using a randomised block design to test the SRFbiochar SP36 fertiliser treatment. The treatments tested were SRFbiocharSP36 as basic fertiliser, SRF-BiocharSP36, SRF-biocharSP36+Cow urine and SRF-BiocharSP36+Cow urine+Azotobacter on tobacco morphological characters, including: plant height, number of leaves, stem diameter, flag leaf angle and wet weight of tobacco leaves. The Research found that SRF-BiocharSP36, used as a basic fertiliser, produced the best results and significantly affected plant height (68.60 cm) and stem diameter (19.39 mm). Apart from that, this formula gave the best results for the number of leaves (24) and the wet weight of leaves (44.92 g).